Comparing absolute and standardized drought indices for modelling tree mortality of spruce, beech, pine, and oak based on the Crown Condition Survey in Germany - Laura-Marie Schotte; Angelika Olesch; Sebastian Fuchs; Luca Smekal; Bernd Ahrends (Forest Ecology and Management, 2026)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

Behavioral responses to artificial skyglow vary in coastal invertebrate larvae - Corie L. Charpentier; Danielle K. Barnes; Saige-Lyn Gidzinski; Laura Jones; Heidi L. Fuchs (Marine Environmental Research, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Applicability and limitations of high-throughput algal growth rate measurements using in vivo fluorescence in microtiter plates - Martin Albrecht; Samira Khanipour Roshan; Laura Fuchs; Ulf Karsten; Rhena Schumann (Journal of Applied Phycology, 2022)
Micro-algae play important roles in primary production, nutrient cycling, and applied biotechnology. Mico-algae are phylogenetically, morphologically and physiologically diverse and often easy to grow in cultures. Growth is the key parameter of viability and crucial for survival in situ and efficiency in vitro . Therefore, growth is often used in eco-physiological experiments to describe the fundamental niche and optimum conditions. In vivo chlorophyll- a fluorescence (IVCF) is a well-established proxy for the growth of micro-algae and is based on constant cell properties during exponential growth. High-throughput IVCF measurements have been applied for about 20 years for few, mostly green algal strains. Here, we tested the IVCF using microtiter plates on strains of four different algal phyla (Chlorophyceae, Cyanobacteria, Bacillariophyceae, Rhodophyceae) and compared the data with cell counts and chlorophyll contents. The microtiter plate reader based IVCF (MPR-IVCF) approach worked best for the diatom Cylindrotheca closterium and the cyanobacterium Synechococcus elongatus . Differences between IVCF and cell count-based growth rates were found for Chlorella vulgaris and Rhodella sp. The IVCF growth rates were lower than the growth rates based on cell counts in both cases, thus underestimating absolute growth rates. The MPR-IVCF method is robust in terms of light scattering and non-photosynthetic contamination but prone to changes in light regimes and also to aggregating algal cells. Thus, we recommend using the MPR-IVCF approach (1) for diatoms and cyanobacteria as an absolute growth rate measure, (2) for relative measures of growth rates, intra and interspecific during the same experiment, also for all algal phyla except Rhodophyta.

Correction to: Increased DNA Damage and Apoptosis in CDKL5-Deficient Neurons - Manuela Loi; Stefania Trazzi; Claudia Fuchs; Giuseppe Galvani; Giorgio Medici; Laura Gennaccaro; Marianna Tassinari; Elisabetta Ciani (Molecular Neurobiology, 2020)

Increased DNA Damage and Apoptosis in CDKL5-Deficient Neurons - Manuela Loi; Stefania Trazzi; Claudia Fuchs; Giuseppe Galvani; Giorgio Medici; Laura Gennaccaro; Marianna Tassinari; Elisabetta Ciani (Molecular Neurobiology, 2020)

Direct‐geneFISH: a simplified protocol for the simultaneous detection and quantification of genes and rRNA in microorganisms - Jimena Barrero‐Canosa; Cristina Moraru; Laura Zeugner; Bernhard M. Fuchs; Rudolf Amann (Environmental Microbiology, 2017)
Summary Although fluorescence in situ hybridization (FISH) with specific ribosomal RNA (rRNA)‐targeted oligonucleotides is a standard method to detect and identify microorganisms, the specific detection of genes in bacteria and archaea, for example by using geneFISH, requires complicated and lengthy (> 30 h) procedures. Here we report a much improved protocol, direct‐geneFISH, which allows specific gene and rRNA detection within less than 6 h. For direct‐geneFISH, catalyzed amplification reporter deposition (CARD) steps are removed and fluorochrome‐labelled polynucleotide gene probes and rRNA‐targeted oligonucleotide probes are hybridized simultaneously. The protocol allows quantification of gene copy numbers per cell and the signal of the directly labelled probes enables a subcellular localization of the rRNA and target gene. The detection efficiencies of direct‐geneFISH were first evaluated on Escherichia coli carrying the target gene on a copy‐control vector. We could show that gene copy numbers correlated to the geneFISH signal within the cells. The new protocol was then applied for the detection of the sulfate thiolhydrolase ( soxB ) genes in cells of the gammaproteobacterial clade SUP05 in Lake Rogoznica, Croatia. Cell and gene detection efficiencies by direct‐geneFISH were statistically identical to those obtained with the original geneFISH, demonstrating the suitability of the simpler and faster protocol for environmental samples.

CASPASE-12 and rheumatoid arthritis in African-Americans - Laura Marshall; Mohammad Obaidullah; Trista Fuchs; Naomi S. Fineberg; Garland Brinkley; Ted R. Mikuls; S. Louis Bridges; Evan Hermel (Immunogenetics, 2014)

Morphological and biological characterization of cell line developed from bovine Echinococcus granulosus - Claudia I. Echeverría; Dora M. Isolabella; Elio A. Prieto Gonzalez; Araceli Leonardelli; Laura Prada; Alina Perrone; Alicia G. Fuchs (In Vitro Cellular & Developmental Biology - Animal, 2010)

Total antioxidant capacity intake and colorectal cancer risk in the Health Professionals Follow-up Study - Rania A. Mekary; Kana Wu; Edward Giovannucci; Laura Sampson; Charles Fuchs; Donna Spiegelman; Walter C. Willett; Stephanie A. Smith-Warner (Cancer Causes & Control, 2010)

Ecotoxicological assessment of the effects of glyphosate and chlorpyrifos in an Argentine soya field - Norma Casabé; Lucas Piola; Julio Fuchs; María Luisa Oneto; Laura Pamparato; Silvana Basack; Rosana Giménez; Rubén Massaro; Juan C. Papa; Eva Kesten (Journal of Soils and Sediments, 2007)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)